2020
DOI: 10.3390/ijerph17103470
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hearing Aids on Poverty, Quality of Life and Mental Health in Guatemala: Results of a before and after Study

Abstract: There are 466 million people globally with disabling hearing loss, many of whom can benefit from hearing aids. The aim of the study was to assess the impact of providing hearing aids on poverty, mental health, quality of life, and activities, among adults in Guatemala. A nonrandomised before and after study was conducted, with a comparison group to assess for secular trends. Adult cases with bilateral hearing impairment were identified within 150 km of Guatemala City, as well as age- and sex-matched comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
5
0
2
Order By: Relevance
“…All studies were cross-sectional in design, and all analyzed large population-based data sets (n > 1000) with the exception of a single study by Spreckley et al (2020) (n = 441). Of the included studies, 41 found an association between income and hearing loss, and 5 found there was no association between hearing loss and income.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were cross-sectional in design, and all analyzed large population-based data sets (n > 1000) with the exception of a single study by Spreckley et al (2020) (n = 441). Of the included studies, 41 found an association between income and hearing loss, and 5 found there was no association between hearing loss and income.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings revealed the presence of a clinical hearing loss in the absence of symptoms; mild high-frequency hearing loss may go unnoticed unless there is routine monitoring of patients before, during, and post-chemotherapy. Furthermore, permanent sensorineural hearing loss emphasizes the need for possible referrals to other healthcare professionals, including psychologists and occupational therapists as hearing loss may impact on all facets of life [ 55 ]. Additionally, there is an increased need to counsel the patient and significant others, such as partners, children, and friends to facilitate early implementation of communication enhancing strategies and reduce the adverse effects on quality of life associated with hearing impairment [ 55 ], especially in light of the diagnosis of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Hearing aid usage is the most common treatment to reduce the adverse effects, including communication difficulties and cognitive decline, caused by hearing loss [ 66 ]. In addition, the use of hearing aids improves productive time use, quality of life, economic circumstances and mental health for listeners with hearing loss [ 67 ]. In our results, people searched for information on hearing aid benefits or the specification of hearing aids.…”
Section: Discussionmentioning
confidence: 99%